Overview of International Practices and Approaches to Euthanasia Regulation: Attitudes of Society and the Medical Community, Potential for Assertiveness - Stashenko, Станіслав (Psychosomatic Medicine and General Practice, 2024)
Relevance. In the modern world, the issue of euthanasia remains one of the most complex and controversial topics in the field of medical ethics, palliative care, as well as psychosocial and legal aspects. The question of euthanasia touches not only on human rights but also on the deep moral and philosophical principles of society, which form the foundation of humanity, support, and the perception of the value of human life, sparking heated debates among doctors, lawmakers, religious leaders, and ordinary citizens. On the one hand, euthanasia can be viewed as an expression of humanism, allowing individuals to avoid unbearable pain and end their lives with dignity; on the other hand, there are serious risks of abuse and violations of the rights of the most vulnerable groups, such as the elderly, patients with incurable, terminal, chronic diseases, and those with mental disorders. Approaches to the regulation of euthanasia vary significantly across different countries, which calls for deep analysis, comparison of practices, and understanding of the social, psychological, and legal aspects of this complex phenomenon. In light of new global trends emphasizing individual rights, technological innovations, and social changes, the study of euthanasia has become extremely relevant and necessary to find balanced solutions. Aim. Conduct a comprehensive analysis of the practices and attitudes towards euthanasia in various countries around the world, focusing on the legislative, social, psychological, and ethical aspects. Examine the current approaches to euthanasia regulation and assess the impact of these approaches on vulnerable population groups, the medical community, and society as a whole. Outline global trends and future perspectives in this area, taking into account technological innovations and the ethical challenges humanity may face in the future. Materials and methods. Scientific publications, legislative acts, international agreements, public opinion surveys, and sociological studies related to the existing legal norms in countries where euthanasia is legalized, as well as in those where it remains prohibited. Research methods include a comparative analysis of legislative systems, quantitative analysis of survey and sociological data, and qualitative analysis of scientific and journalistic literature that addresses various aspects of euthanasia. Conclusions. Euthanasia remains an extremely complex and multifaceted issue, as it is intertwined with ethical, legal, social, and psychological aspects, deeply connected to the cultural and religious traditions of societies. The analysis of practices in different countries shows that the legalization of euthanasia can help ensure the right to a dignified death, particularly for patients with incurable diseases. However, significant risks related to potential abuses and pressures on vulnerable groups, such as the elderly, patients with incurable, terminal, chronic illnesses, and those with mental disorders, remain serious obstacles to achieving a global consensus. Social attitudes and the views of the medical community vary greatly—from support for personal autonomy to concerns about the moral responsibility of healthcare professionals. Moreover, the rise of technological advancements, particularly the development of artificial intelligence and life-support systems, poses new challenges for regulating euthanasia, requiring legislative frameworks to adapt to new realities. In the future, debates on euthanasia are likely to intensify in the face of global changes, and further research and analysis will be necessary to find a fair and balanced approach to this issue.